Perancangan Sistem Informasi Akuntansi Untuk Akuntabilitas Keuangan di KBIHU Hafas - Irma Yunita; Ahmad Homaidi; Lukman Fakih; Taufik Saleh; Jarot Dwi; Zaehol Fatah (Jurnal Aplikasi Teknologi Informasi dan Manajemen (JATIM), 2022)
The financial management carried out by this institution is still carried out in a semicomputerized manner, namely by recording payment data using Ms. Excel which is done whenneeded to recapitulate financial statements. This of course has an impact on the speed andaccuracy of the services provided. In conducting this research using the waterfall method, thestages are communication, planning, modeling, construction, and deployment. Using this method,it is possible that the downstream stages that must be carried out can be well organized so that theexpected results are following the needs. The results obtained in the design of this accountinginformation sistem can make it easier for officers to make accounting-standard financial reportsthat will be reported to the leadership. Besides that, it can also provide optimal service to thecongregation. Thus this information sistem can improve the quality of services provided byKBIHU Hafas to be more effective and efficient.